2023
DOI: 10.1007/s10896-022-00488-1
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies in Women and Children Living with Domestic Violence: Staying Alive

Abstract: Purpose Children exposed to domestic violence are at risk of adverse short- and long-term psychosocial effects and of being abused themselves. However, mothers and children face systemic gaps when seeking safety from domestic violence services and police. Safety planning typically focuses on women, overlooking their multiple social identities and excluding their children. We explored safety strategies used by mothers and children coping together with severe domestic violence. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In contrast, what our participants have indicated helped, or would have helped, are services which understand, listen and support them to exercise agency in their lives (Katz, 2016). Such is the approach summarized in Morris et al, 2020 article which outlines attitudes that bolster children's agency and abilities, including recognizing and acknowledging children's abilities in utilizing support systems and co-constructing resiliency within the family (see also Winfield et al, 2023). Indications that this would have been helpful were common amongst participants of all genders and both age groups.…”
Section: Recommendations For Preventative Policy and Practicementioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, what our participants have indicated helped, or would have helped, are services which understand, listen and support them to exercise agency in their lives (Katz, 2016). Such is the approach summarized in Morris et al, 2020 article which outlines attitudes that bolster children's agency and abilities, including recognizing and acknowledging children's abilities in utilizing support systems and co-constructing resiliency within the family (see also Winfield et al, 2023). Indications that this would have been helpful were common amongst participants of all genders and both age groups.…”
Section: Recommendations For Preventative Policy and Practicementioning
confidence: 84%
“…Children's ages, gender, coping abilities and supports in the societal context have been found to influence the outcomes associated with growing up in DV (Barnes et al, 2022;Clements et al, 2008;Yule et al, 2019). Research indicates that the extent to which children are able to cope with DV is linked to their mothers' capacity to maintain close relationships and protect their children as well as they can (Buchanan, 2018;Winfield et al, 2023). Further, research by O'Brien et al (2013) found that the potential threat to a child's immediate and long-term wellbeing can be reduced by them establishing a safe place and a supportive relationship outside the family home.…”
Section: Outcomes Of Growing Up With DVmentioning
confidence: 99%